Cholesterol Granuloma as a Rare Differential in Bone Erosion of the Orbit: A Case Report - Mary Rose Pe Yan MD; Gian Carlo Aurelio MD; Felice Katrina T. Ranche MD (Philippine Journal of Ophthalmology)
Objectives: We report a case of orbitofrontal cholesterol granuloma as a rare differential diagnosis of orbital erosion in the diploe of the frontal bone.